Comprehensive measurement techniques and multi-index correlative evaluation approach for structural health monitoring of highway bridges. (February 2020) - Zhou, Cuiying; Wu, Yongtian; Cui, Guangjun; Zhang, Aobo; Gao, Yi; Wang, Xiangdong; Ouyang, Jinwu; Sun, Hao; Liang, Yanhao; Liu, Zhen; Zhang, Lihai
Highlights: Bridges are vulnerable to damage due to subtropical weather and geological conditions. A multi – factor correlation method is used to monitor highway bridge health condition. The method takes the parameter variation synthesis coefficient as the core to model. HSCMS is an effective and accurate way to monitor the health condition of bridges. Results provide a technical basis for monitoring of bridges under the same conditions. Abstract: The bridge is damaged under the long-term traffic load, climate and geological conditions, which may lead to serious traffic interruption and economic loss. This study presents an integrated measurement technique in conjunction with a multi-index correlative evaluation approach for structural condition assessment of bridges. Using a typical highway bridge in China as a case study, the concrete strength, thickness of bridge deck pavement, thickness of the bottom plate of the hollow plate, crack development, cover thickness of steel bars etc. were systematically monitored. Most importantly, a series of static load tests were conducted and the results were analysed using a developed multi-index correlative evaluation model to assess the current structural capacity of the bridge. The results show that comprehensive measurements and the multi-index correlative evaluation approach provide an effective means for structural health monitoring of bridges, and can provide theoretical basis for the highway bridge monitoring under similar complicated environmental conditions.